Population and Development: Employing the Capability Approach in Family Planning Policy for Women in Indonesia - Julius Ary Mollet; Genoveva Chatleen C. Mollet (International Journal of Applied Business and International Management, 2024)
Indonesia currently holds the position of the fourth most populous country globally, facing persistent challenges such as poverty, hunger, gender inequality, and disparity. In response, a family planning program was initiated in the 1980s to regulate population growth. Using the capability approach, this research investigates the impact of Indonesia's family planning policy on women, emphasizing gender disparity resulting from inadequate support for human rights in population and family development. Conversion factors play a significant role in shaping women's freedom and capabilities. The study critically examines the strengths and weaknesses of the family planning policy, revealing obstacles for women related to governance shifts, conflicting policies, government inefficiencies, and BKKBN's limitations. The study underscores the importance of effective implementation across all sectors and agencies to address gender inequality in women's health.